Strategi dan Inovasi Pemasaran dalam Mempertahankan Stabilitas Omzet Vitamin C (Brand Hevit-C) Selama dan Pasca Covid-19 di Apotek Wilayah Jakarta - Piter Piter; Anisa Indah Saputrie (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The Covid-19 pandemic has significantly altered the landscape of the healthcare product market, with a rapid increase in demand for Vitamin C as a means to enhance immune function. Amidst intensifying competition, Hevit-C, a well-known brand in Jakarta's pharmacies, has employed marketing strategies and innovations to maintain its revenue stability. This study aims to analyze various marketing strategies and innovations implemented by Hevit-C during and post-pandemic, and to identify the correlation between these strategies and innovations with the brand's revenue stability. The research methodology includes sales data analysis, collection of data related to marketing strategies and innovations used by product management, and a review of literature on marketing strategies in the pharmaceutical industry. It is anticipated that the findings of this research will benefit healthcare professionals and pharmacies by providing insights and educational materials on the use of Vitamin C for patients and the general public. Furthermore, the study aims to benefit the pharmaceutical industry by optimizing marketing strategies and better meeting market demands.